Using Hermetia illucens to process Ugandan waragi waste. (20th February 2019) - Dobermann, Darja; Field, Lin M.; Michaelson, Louise V.
Abstract: Waragi, a form of homemade gin, is produced throughout Uganda in both legal and illegal breweries. Waste produced during the illegal brewing process is predominantly disposed of via indiscriminate dumping into surrounding environments and reports from local communities have indicated this to be harmful to crops and livestock. The larvae of Hermetia illucens are documented to consume a wide range of otherwise unappealing waste products. In addition to this, the prepupal stages of the larvae can serve as a high-quality protein feed for animal livestock. Therefore, the feasibility of the larvae of H. illucens to digest waragi waste was evaluated. A dietary toxicity trial was run to establish an LC50 value for waragi inclusion in larval diets. This was followed by a larger scale trial utilising waragi waste in combination with various in situ available feed stuffs to further assess the viability of processing waragi waste using H. illucens. Larvae were able to eat diets composed of up to 85% waragi waste without any significant impact ( p  > .01) on survival or growth. When combined with locally available feed sources, e.g. chicken offal, cottonseed cake, sunflower meal or groundnut cake, larvae showed high survival (>95%) and growth rates on diets including 25% waragi waste. Results indicate that H. illucens larvae may be a useful tool in processing waragi waste. Graphical abstract: Highlights: Hermetia illucens larvae are examined as a possible mechanism to valorise waragi waste. Toxicity trials show no significant impact on growth or survival up to 85% dietary waragi waste inclusion. 25% waragi waste combined with additional in situ waste products demonstrated high survival and growth rates of larvae. Diets containing waragi waste had no impact on subsequent development and reproduction of H. illucens.